From encomenderos to neoliberals that remain encomenderos in the Peruvian Right - Lynch, Nicolás (2020)
This article places the origin and development of the Peruvian Right as a neoliberal right over the period 1990-2020. The study delves into the roots of this political notion in Peruvian history, and compares it to previous rights. At the beginning of the examined period, during Fujimorism, it is an authoritarian right. Subsequently, it becomes a right that ensures the continuity of the model while it transitions to democracy. However, it is an unfinished transition as the neoliberal continuity promotes a limited democracy, represented by politicians but run by technocrats, and policed by large business owners. Corruption scandals in recent years have revealed the exhaustion of this arrangement, and in the absence of an alternative two factions of neoliberalism compete for finding a way out, the remains and heirs to Fujimorism, and the one born in democracy. Neither has yet proven able to define the situation, which could make room for a third actor.